Identification of Podocyte Cargo Proteins by Proteomic Analysis of Clathrin-Coated Vesicles - Groener, Marwin; Wang, Ying; Cross, Elizabeth; Tian, Xuefei; Ebenezer, Karen; Baik, Eunice; Pedigo, Christopher; Schiffer, Mario; Inoue, Kazunori; Ishibe, Shuta (Kidney360, 2020)
Background Clathrin-mediated endocytosis (CME) plays a fundamental role in podocyte health. Genetic ablation of genes implicated in CME has been shown to cause severe proteinuria and foot process effacement in mice. However, little is known about the cargo of clathrin-coated vesicles (CCVs) in podocytes. The goal of this study was to isolate CCVs from podocytes and identify their cargo by proteomic analysis. Methods Glomeruli isolated from Podocin-Cre Rosa-DTR flox mouse kidneys were seeded and treated with diphtheria toxin to obtain pure primary podocyte cultures. CCVs were isolated by differential gradient ultracentrifugation, and enrichment of CCVs was assessed by immunoblotting and electron microscopy (EM). Liquid chromatography-mass spectrometry (LC-MS) was performed for proteomic analysis. Proteins with higher abundance than transferrin receptor protein 1 were evaluated for CCV cargo potential against previously published literature. Immunofluorescence staining of identified cargo proteins and CCVs was performed in podocytes for further verification. Results Immunoblotting for multiple protein markers of CME revealed enrichment in the CCV fraction. Enrichment of CCVs among other small vesicles was observed via EM. Proteomics yielded a total of >1200 significant proteins. Multiple-step data analysis revealed 36 CCV-associated proteins, of which 10 represent novel, highly abundant cargo proteins in podocytes. Colocalization of cargo proteins and CCVs on immunostaining was observed. Conclusions Our identification of podocyte CCV cargo proteins helps to elucidate the importance of endocytic trafficking for podocyte health and maintenance of the glomerular environment.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Basic Science; clathrin-coated vesicles; clathrin-mediated endocytosis; glomerular and tubulointerstitial diseases; glomerular diseases; immunoblotting; kidney glomerulus; mice; podocytes; proteomics